Nano-sized warriors: zinc chromium vanadate nanoparticles as a dual solution for eradicating waterborne enterobacteriaceae and fighting cancer - Rehman, Suriya; Alahmari, Fatimah; Aldossary, Laila; Alhout, Maryam; Aljameel, Suhailah S.; Ali, Syed Mehmood; Sabir, Jamal S. M.; Khan, Firdos Alam; Rather, Irfan A. (Frontiers in Pharmacology, 2023)
The revolution of biomedical applications has opened new avenues for nanotechnology. Zinc Chro-49 mium vanadate nanoparticles (VCrZnO4 NPs) have emerged as an up-and-coming candidate, with 50 their exceptional physical and chemical properties setting them apart. In this study, a one-pot sol-51 vothermal method was employed to synthesize VCrZnO4 NPs, followed by a comprehensive struc-52 tural and morphological analysis using a variety of techniques, including X-Ray diffraction, scan-53 ning electron microscopy, high-resolution transmission electron microscopy, Energy-dispersive X-54 ray, and X-ray photoelectron spectroscopy. These techniques confirmed the crystallinity of the NPs. 55 The VCrZnO4 NPs were tested for their antibacterial activity against primary contaminants such as 56 Enterobacteriaceae, including Shigella flexneri, Salmonella cholerasis, and Escherichia coli, commonly 57 found in hospital settings, using the broth dilution technique. The results indicated a stronger anti-58 bacterial activity of VCrZnO4 NPs against Shigella and Salmonella than E. coli. Electron microscopy 59 showed that the NPs caused severe damage to the bacterial cell wall and membrane, leading to cell 60 death. In addition, the study evaluated the anticancer activities of the metal complexes in vitro using 61 colorectal cancer cells (HCT-116) and cervical cancer cells (HELA), along with non-cancer cells and 62 human embryonic kidney cells (HEK-293). A vanadium complex demonstrated efficient anticancer 63 effects with half-inhibitory concentrations (IC50) of 38.50+3.50 g/mL for HCT-116 cells and 42.25+4.15 64 g/mL for HELA cells. This study highlights the potential of Zinc Chromium vanadate nanoparticles 65 as promising candidates for antibacterial and anticancer applications. Various advanced character-66 ization techniques were used to analyze the properties of nanomaterials, which may help develop 67 more effective and safer antibacterial and anticancer agents in the future.